Conceptual safeguards method proposal for milling facilities based on nuclear isotopic ratios in uranium mill tailings - Danwoo Ko; Seunguk Cheon; Jiyoung Kim; Seungmin Lee; Seung Min Woo (Nuclear Engineering and Technology)
There is an argument that the Comprehensive Safeguards Agreement (CSA) should be applied to the milling process, which is the first stage of nuclear fuel cycle, to reduce the possibility of nuclear proliferation. Therefore, this study aims to propose new and conceptual safeguards applicable to milling facilities and design Nuclear Material Accountancy for its application. Mill tailings reach a secular equilibrium state. While approaching this equilibrium state, the ratio of each isotope changes. First, the Bateman equation was used to analyze this phenomenon and evaluate the feasibility of utilizing the specific isotope ratio to track undeclared nuclear activities. Second, the gamma spectrum analysis of mill tailings was conducted using the Monte Carlo N-Particle Code to validate undeclared nuclear activities. This study shows that the ratio of U-235/Th-234 and U-235/Pa-234m can estimate the production time within a year. Furthermore, gamma spectrum analysis of mill tailings revealed visible differences in the low-energy region due to the decay of Th-234. Finally, a conceptual Material Balance Area, Key Measurement Points, and Material Balance Period for milling facilities were designed to apply CSA. It is anticipated that applying CSA to milling facilities could enhance not only the nuclear fuel cycles but also nuclear non-proliferation system.